THE INFLUENCE OF PSYCHOLOGICAL CAPITAL AND TRANSFORMATIONAL LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE : (A STUDY ON EMPLOYEES OF PT BIO FARMA (PERSERO) - Kurniawan, Aji Muhamad; Dwijayanty, Rima (Politeknik Negeri Ambon, 2025)
Introduction: This study analyzes the influence of Psychological Capital and Transformational Leadership Style on Employee Performance at PT Bio Farma (Persero), a state-owned pharmaceutical enterprise. Methods: Data were collected using a quantitative survey of 300 employees and tested for validity, reliability, and classical assumptions before being analyzed with multiple regression. Results: The results show that Psychological Capital and Transformational Leadership have positive and significant effects on employee performance, explaining 59.2% of its variance. Psychological Capital contributes through self-efficacy, hope, optimism, and resilience, while transformational leadership strengthens performance by inspiring, stimulating, and personally supporting employees. These findings highlight the importance of integrating psychological empowerment and effective leadership to build a productive and adaptive work environment. The managerial implication is that PT Bio Farma should implement training programs to enhance psychological capital and develop transformational leadership skills to sustain employee performance and organizational competitiveness. Keywords: Psychological Capital, Transformational Leadership, Employee Performance